2010
DOI: 10.1021/ie9010518
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Paints with Zinc “Tannate”

Abstract: During the past decade, the necessity of new ecofriendly antifouling pigments was established. Among these new pigments, special attention should be paid to tannin and its derivatives. Tannins are synthesized by plants as part of their defense mechanism against the attack of pathogens. The objective of this work was to study the antifouling efficiency of paints containing zinc "tannate" in artificial seawater. The zinc "tannate" was precipitated at pH 4 and pH 8. Insoluble and soluble matrix antifouling paints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Consequently, because of the above-mentioned problems, International Maritime Organization banned the use of tributyltin since September 2008 [1,15]. Since the banning of tributyltin and other tin-based compounds, the tin is replaced by other metals like zinc [16], titanium and mostly copper [17,18]. Copper has good antifouling properties against some of the biofouling organisms like algae and barnacles [19], but copper can concentrate in shellfish tissues and has negative impacts on developing vertebrates and invertebrates [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, because of the above-mentioned problems, International Maritime Organization banned the use of tributyltin since September 2008 [1,15]. Since the banning of tributyltin and other tin-based compounds, the tin is replaced by other metals like zinc [16], titanium and mostly copper [17,18]. Copper has good antifouling properties against some of the biofouling organisms like algae and barnacles [19], but copper can concentrate in shellfish tissues and has negative impacts on developing vertebrates and invertebrates [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…So, an optimization of formulations and biocide release profiles is essential. For example, Bellotti et al have shown that antifouling paints with zinc "tannate" are promising, nevertheless, antifouling efficiency was dependent on the formulation: the matrix and the plasticizer employed modified the antifouling activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, TBT and other tin-based antifouling agents are banned by the International Marine Organization (IMO) 15 . TBT-free formulations, in which tin is replaced by metals like copper 5,8,16 , zinc 17 and titanium 18 , are in use today. Although copper is essential for all forms of life due to cellular processes, it is considered toxic when tolerance limits are exceeded 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The degree of fouling attachment was evaluated every month and distances less than 1.3 cm from the edge of samples were not considered 17,34 . The antifouling efficiency of the coating was carried out according to the fouling coverage area.…”
mentioning
confidence: 99%